Kinetic Study on Coagulation Process with Poly Aluminium Chloride and Alum Coagulants in Treating The Liquid Waste of Tempeh Industry - Iqbal Syaichurrozi (Eksergi, 2021)
Several factors that influence the coagulation process in reducing chemical oxygen demand (COD) in wastewater are processing time, coagulant dose and type of coagulant. The effect of these three factors on the reduction of COD in tempeh industrial wastewater during the coagulation process has been investigated by Hidayah (2018). However, kinetic studies in depth have not been done by Hidayah (2018). Therefore, the aim of this study was to develop a new kinetic model that can predict the performance of the coagulation process. It is hoped that the kinetic model can be used in a wider range of operating conditions. In this study, the pseudo first order and pseudo second order kinetic models were tested to get the best model. Based on simulation results, both models produced almost the same accuracy. For reason of simplification, the pseudo first order model was chosen as the basic model in this study. Furthermore, modifications were made to the pseudo first order model so that the effect of processing time, coagulant dose and type of coagulant appeared in the model. This kinetic model was successfully tested to predict the coagulation performance of study of Hidayah (2018) with an average Mean Absolute Percentage Error (MAPE) of 10.8%.